A Comment on "Information and Spillovers from Targeting Policy in Peru's Anchoveta Fishery" - Marta Bernardi; Sarah Zeller; Rebecca Rotich (Institute for Replication (I4R), 2024)
The study provides empirical evidence that a targeted policy can backfire because information signals affect non-targeted units. Specifically, the analysis of the policy aimed at regulating the harvesting of juvenile fish in Peru's Anchovy Fishery, by temporarily closing areas with high juvenile catch percentages, reveals an unintended increase of 48% in the overall seasonal juvenile catch percentage. This appears to be due to substantial spatial and temporal spillovers generated by the policy that reduces search costs for fishers. The study combines administrative micro-data used by the regulator to generate closures with biologically richer data from fishing firms. All results are easily computationally reproducible within a 5-hour time frame, except for the synthetic controls robustness check, which takes a considerable amount of time (appr. 64 hours) but works. We stress the robustness and reproducibility of the study by testing whether the analysis is robust to the use of different types of standard errors, and the findings appear unaffected. Overall, the full analysis and graphic outputs of the paper are reproducible using the publicly available complementary data and code from the AEJ website despite minor code interpretability challenges.
Keywords: Q28; O13; Q56; D83; Q22; 330; information spillovers; targeted policies; place-based policies; fisheries; Peru